Human Immunodeficiency Virus–Associated Myocardial Diastolic Dysfunction and Soluble ST2 Concentration in Tanzanian Adults: A Cross-Sectional Study. (11th June 2020) - Kingery, Justin R; Goyal, Parag; Hosalli, Rahul; Lee, Myung Hee; Desderius, Bernard; Kalokola, Fredrick; Makubi, Abel; Fadhil, Salama; Kapiga, Saidi; Karmali, Dipan; Kaminstein, Daniel; Devereux, Richard; et al.
Abstract: Background: The aims of this study were (1) to compare the prevalence of myocardial diastolic dysfunction (DD) in antiretroviral therapy (ART)–naive people living with human immunodeficiency virus (PLWH) to human immunodeficiency virus (HIV)–uninfected adults in East Africa and (2) to determine the association between serum concentration of the cardiac biomarkers ST2 and DD. Methods: In this cross-sectional study, we enrolled PLWH and uninfected adults at a referral HIV clinic in Mwanza, Tanzania. Standardized history, echocardiography, and serum were obtained. Regression models were used to quantify associations. Results: We enrolled 388 ART-naive PLWH and 461 HIV-uninfected adults with an average age of 36.0 ± 10.2 years. Of PLWH in the third, fourth, and fifth decades of life, 5.0%, 12.5%, and 32.7%, respectively, had DD. PLWH had a higher prevalence of DD (adjusted odds ratio, 2.71 [95% confidence interval, 1.62–4.55]; P < .0001). PLWH also had a higher probability of dysfunction with one or fewer traditional risk factors present. Serum ST2 concentration was associated with dysfunction in PLWH but not uninfected participants ( P = .04 and P = .90, respectively). Conclusions: In a large population of young adults in sub-Saharan Africa, DD prevalence increased starting in the third decade of life. HIV was independently associated with dysfunction. Serum ST2 concentration was associated with DD in PLWH but not HIV-uninfected participants. This pathway may provide insight into the mechanisms of HIV-associated dysfunction. Abstract : The prevalence of myocardial diastolic dysfunction was 2-fold higher in young HIV-infected, antiretroviral therapy–naive Tanzanian adults as compared to those uninfected. Serum concentration of the biomarker ST2 was associated with dysfunction in HIV-infected but not uninfected participants.